2003
DOI: 10.1108/02635570310470647
|View full text |Cite
|
Sign up to set email alerts
|

Did your efforts really win customers’ satisfaction?

Abstract: 1998),"Customer loyalty and complex services: The impact of corporate image on quality, customer satisfaction and loyalty for customers with varying degrees of service expertise"If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Prior research has shown that efforts can attract more patients and increase doctors' popularity (Mcclean and Collins, 2011;Chien et al, 2003). Regarding central efforts, log-in frequency is correlated to service provision.…”
Section: Efforts and Service Quantitymentioning
confidence: 99%
“…Prior research has shown that efforts can attract more patients and increase doctors' popularity (Mcclean and Collins, 2011;Chien et al, 2003). Regarding central efforts, log-in frequency is correlated to service provision.…”
Section: Efforts and Service Quantitymentioning
confidence: 99%
“…The fourth determining factor of hotel efficiency that is specified is "customer satisfaction." It is expected that greater customer satisfaction will have a positive effect on efficiency because it favors a greater market share, reduced price elasticity and reduced costs, especially those associated with attracting new customers (Chien, Chang, & Su, 2003). Despite its importance, previous research does not yet provide evidence that customer satisfaction is a determinant of hotel efficiency.…”
Section: Price Of Other Operations Costs (Wmentioning
confidence: 99%
“…These results of customer satisfaction are consequences factors such as complaints or loyalty of customer (Johnson et al, 2001). Each factor in the ECSI model is a latent construct which is operationalized by multiple indicators (Fornell, 1992;Chien et al, 2002).…”
Section: Literature Review About Customer Satisfaction Index (Csi) Modelmentioning
confidence: 99%